1994
DOI: 10.1111/j.1751-1097.1994.tb05092.x
|View full text |Cite
|
Sign up to set email alerts
|

Distance‐dependent Fluorescence Quenching of Tryptophan by Acrylamide

Abstract: We used GHz frequency-domain fluorometry to investigate the time-dependent intensity decays of N-acetyl-L-trytophanamide (NATA) when collisionally quenched by acrylamide in propylene glycol at 20 degrees C. The intensity decays of NATA became increasingly heterogeneous in the presence of acrylamide. The NATA intensity decays were not consistent with the Collins-Kimball radiation boundary condition (RBC) model for quenching. The steady-state Stern-Volmer plots show significant upward curvature. At low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…The Stern-Volmer quenching constant K D quantitatively describes this accessibility [45, 46]. The K D values for W 601 , W 669 and N-acetyl tryptophanamide were determined under native and denatured conditions using acrylamide as a quencher.…”
Section: Resultsmentioning
confidence: 99%
“…The Stern-Volmer quenching constant K D quantitatively describes this accessibility [45, 46]. The K D values for W 601 , W 669 and N-acetyl tryptophanamide were determined under native and denatured conditions using acrylamide as a quencher.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested that dynamical quenching can occur via a distance-dependent through-space interaction, 61,62 although the quencher must still approach within 3 Å of the fluorophore. 61,62 Trp87 resides >8 Å from the closest approach to bulk solvent, rendering it too far within the protein core to have random long-range interactions that distort the quenching behavior.…”
Section: Discussionmentioning
confidence: 99%
“…5) In this expression b depends on quencher concentration and diffusion coefficient. Such decays can be resolved by multi-exponential models but that would be erroneous since the decays are non-exponential due to a distance-dependent occasional interaction with the quencher [39,40]. The best model to fit these non-exponential decays with a single exponent is a lifetime distribution model.…”
Section: Effect Of Fluorescence Quenching On 2ap Lifetime Distributionmentioning
confidence: 99%
“…The best model to fit these non-exponential decays with a single exponent is a lifetime distribution model. We used acrylamide to quench 2AP fluorescence in a highly viscous solution (80:20 glycerol:water mixture) to detect the transient effect clearly [39,40]. One molar acrylamide quenches 2AP fluorescence by 50% with no detectable spectral shift ( Figure 4).…”
Section: Effect Of Fluorescence Quenching On 2ap Lifetime Distributionmentioning
confidence: 99%